Math Practice Online > free > lessons > New York > 9th grade > System of Equations Addition

These sample problems below for System of Equations Addition were generated by the MathScore.com engine.

## Sample Problems For System of Equations Addition

### Complexity=3

Solve. Answer in the form (x,y). For example: (-2,3)
 1.   -x + 3y = - 1x - y = 1 Answer (x,y): 2.   x + y = - 42x + y = - 7 Answer (x,y):

### Complexity=5

Solve. Answer in the form (x,y). For example: (-2,3)
 1.   2x - 5y = - 2- 3x - y = - 14 Answer (x,y): 2.   2x - 3y = 4x - y = 1 Answer (x,y):

### Complexity=10

Solve. Answer in the form (x,y). For example: (-2,3)
 1.   6x - y = 37- 7x - 4y = - 7 Answer (x,y): 2.   10x - 7y = 104- 9x - 8y = - 65 Answer (x,y):

### Complexity=13

Solve. Answer in the form (x,y). For example: (-2,3)
 1.   - 2x - y = - 23-x + 2y = 21 Answer (x,y): 2.   -x + 9y = 1- 8x + y = 79 Answer (x,y):

### Complexity=14

Solve. Answer in the form (x,y). For example: (-2,3)
 1.   -x - y = 8- 3x + 2y = - 41 Answer (x,y): 2.   - 9x + 5y = - 11- 2x - y = 25 Answer (x,y):

### Complexity=15

Solve. Answer in the form (x,y). For example: (-2,3)
 1.   x - y = 07x + 5y = 168 Answer (x,y): 2.   2x + 13y = 17311x - 6y = - 211 Answer (x,y):

### Complexity=3

Solve. Answer in the form (x,y). For example: (-2,3)
1
-x + 3y = - 1
x - y = 1

Solution
-x + 3y = - 1
x - y = 1

Add the equations to eliminate x.
-x + 3y = - 1
+ [ x - y = 1 ]
2y = 0

Now solve for y
Divide by 2

y = 0

Now plug value of y into the original first equation
-x + 3(0) = - 1
-x = - 1
Multiply by - 1
 -x(- 1) = -(- 1)

x = 1

2
x + y = - 4
2x + y = - 7

Solution
x + y = - 4
2x + y = - 7

Subtract the equations to eliminate y.
x + y = - 4
- [ 2x + y = - 7 ]
x + y + - 2x + -y = 3

Now solve for x
Multiply by - 1
 -x(- 1) = 3(- 1)

x = - 3

Now plug value of x into the original first equation
- 3 + y = - 4
y - 3 = - 4
y - 3 + 3 = - 4 + 3
y = - 1

### Complexity=5

Solve. Answer in the form (x,y). For example: (-2,3)
1
2x - 5y = - 2
- 3x - y = - 14

Solution
2x - 5y = - 2
- 3x - y = - 14

Multiply the second equation by 5
2x - 5y = - 2
- 15x - 5y = - 70

Subtract the equations to eliminate y.
2x - 5y = - 2
- [ - 15x - 5y = - 70 ]
2x - 5y - (- 15x - 5y) = 68

Now solve for x
Divide by 17

x = 4

Now plug value of x into the original first equation
2(4) - 5y = - 2
- 5y + 8 = - 2
- 5y + 8 - 8 = - 2 - 8
- 5y = - 10

Divide by - 5

y = 2

2
2x - 3y = 4
x - y = 1

Solution
2x - 3y = 4
x - y = 1

Multiply the second equation by 2
2x - 3y = 4
2x - 2y = 2

Subtract the equations to eliminate x.
2x - 3y = 4
- [ 2x - 2y = 2 ]
2x - 3y - (2x - 2y) = 2

Now solve for y
Multiply by - 1
 -y(- 1) = 2(- 1)

y = - 2

Now plug value of y into the original first equation
2x - 3(- 2) = 4
2x + 6 = 4
2x + 6 - 6 = 4 - 6
2x = - 2

Divide by 2

x = - 1

### Complexity=10

Solve. Answer in the form (x,y). For example: (-2,3)
1
6x - y = 37
- 7x - 4y = - 7

Solution
6x - y = 37
- 7x - 4y = - 7

Multiply the first equation by 4
24x - 4y = 148
- 7x - 4y = - 7

Subtract the equations to eliminate y.
24x - 4y = 148
- [ - 7x - 4y = - 7 ]
24x - 4y - (- 7x - 4y) = 155

Now solve for x
Divide by 31

x = 5

Now plug value of x into the original first equation
6(5) - y = 37
-y + 30 = 37
-y + 30 - 30 = 37 - 30
-y = 7

Multiply by - 1
 -y(- 1) = 7(- 1)

y = - 7

2
10x - 7y = 104
- 9x - 8y = - 65

Solution
10x - 7y = 104
- 9x - 8y = - 65

Multiply the first equation by 8
Multiply the second equation by 7
80x - 56y = 832
- 63x - 56y = - 455

Subtract the equations to eliminate y.
80x - 56y = 832
- [ - 63x - 56y = - 455 ]
80x - 56y - (- 63x - 56y) = 1287

Now solve for x
Divide by 143

x = 9

Now plug value of x into the original first equation
10(9) - 7y = 104
- 7y + 90 = 104
- 7y + 90 - 90 = 104 - 90
- 7y = 14

Divide by - 7

y = - 2

### Complexity=13

Solve. Answer in the form (x,y). For example: (-2,3)
1
- 2x - y = - 23
-x + 2y = 21

Solution
- 2x - y = - 23
-x + 2y = 21

Multiply the first equation by 2
- 4x - 2y = - 46
-x + 2y = 21

Add the equations to eliminate y.
- 4x - 2y = - 46
+ [ -x + 2y = 21 ]
- 5x = - 25

Now solve for x
Divide by - 5

x = 5

Now plug value of x into the original first equation
- 2(5) - y = - 23
-y - 10 = - 23
-y - 10 + 10 = - 23 + 10
-y = - 13

Multiply by - 1
 -y(- 1) = - 13(- 1)

y = 13

2
-x + 9y = 1
- 8x + y = 79

Solution
-x + 9y = 1
- 8x + y = 79

Multiply the first equation by 8
- 8x + 72y = 8
- 8x + y = 79

Subtract the equations to eliminate x.
- 8x + 72y = 8
- [ - 8x + y = 79 ]
- 8x + 72y + 8x + -y = - 71

Now solve for y
Divide by 71

y = - 1

Now plug value of y into the original first equation
-x + 9(- 1) = 1
-x - 9 = 1
-x - 9 + 9 = 1 + 9
-x = 10

Multiply by - 1
 -x(- 1) = 10(- 1)

x = - 10

### Complexity=14

Solve. Answer in the form (x,y). For example: (-2,3)
1
-x - y = 8
- 3x + 2y = - 41

Solution
-x - y = 8
- 3x + 2y = - 41

Multiply the first equation by 2
- 2x - 2y = 16
- 3x + 2y = - 41

Add the equations to eliminate y.
- 2x - 2y = 16
+ [ - 3x + 2y = - 41 ]
- 5x = - 25

Now solve for x
Divide by - 5

x = 5

Now plug value of x into the original first equation
-(5) - y = 8
-y - 5 = 8
-y - 5 + 5 = 8 + 5
-y = 13

Multiply by - 1
 -y(- 1) = 13(- 1)

y = - 13

2
- 9x + 5y = - 11
- 2x - y = 25

Solution
- 9x + 5y = - 11
- 2x - y = 25

Multiply the second equation by 5
- 9x + 5y = - 11
- 10x - 5y = 125

Add the equations to eliminate y.
- 9x + 5y = - 11
+ [ - 10x - 5y = 125 ]
- 19x = 114

Now solve for x
Divide by - 19

x = - 6

Now plug value of x into the original first equation
- 9(- 6) + 5y = - 11
5y + 54 = - 11
5y + 54 - 54 = - 11 - 54
5y = - 65

Divide by 5

y = - 13

### Complexity=15

Solve. Answer in the form (x,y). For example: (-2,3)
1
x - y = 0
7x + 5y = 168

Solution
x - y = 0
7x + 5y = 168

Multiply the first equation by 5
5x - 5y = 0
7x + 5y = 168

Add the equations to eliminate y.
5x - 5y = 0
+ [ 7x + 5y = 168 ]
12x = 168

Now solve for x
Divide by 12

x = 14

Now plug value of x into the original first equation
14 - y = 0
-y + 14 = 0
-y + 14 - 14 = 0 - 14
-y = - 14

Multiply by - 1
 -y(- 1) = - 14(- 1)

y = 14

2
2x + 13y = 173
11x - 6y = - 211

Solution
2x + 13y = 173
11x - 6y = - 211

Multiply the first equation by 11
Multiply the second equation by 2
22x + 143y = 1903
22x - 12y = - 422

Subtract the equations to eliminate x.
22x + 143y = 1903
- [ 22x - 12y = - 422 ]
22x + 143y + - 22x - - 12y = 2325

Now solve for y
Divide by 155

y = 15

Now plug value of y into the original first equation
2x + 13(15) = 173
2x + 195 = 173
2x + 195 - 195 = 173 - 195
2x = - 22

Divide by 2

x = - 11

MathScore.com

Copyright Accurate Learning Systems Corporation 2008.